A SUSTAINABLE APPROACH TO HIGH SCHOOL EDUCATION: BIOPLASTICS IN CHEMISTRY EDUCATION – PART I - Barros, Marcos Antonio Sousa; Almeida, Pedro (Seven Editora, 2025)
This study aimed to promote environmental awareness among high school students through a didactic sequence exploring bioplastics made from corn starch, integrating chemical concepts with reflections on sustainability. The qualitative and exploratory research was conducted with a class of 34 students at the Federal Institute of Pernambuco – Ipojuca Campus, and involved the application of pre- and post-intervention questionnaires to analyze the evolution of knowledge regarding polymers, conventional plastics, bioplastics, and environmental impacts. The methodology included theoretical lessons, debates, and experimental activities aligned with the Science, Technology, and Society (STS) approach. The results demonstrated a significant improvement in the understanding of the concepts covered, highlighting the connection between theory and practice. The laboratory synthesis of bioplastic proved to be a highly effective teaching resource, promoting student engagement and consolidating learning. All participants reported a stronger connection between theoretical content and its everyday applications. Most students showed awareness of the importance of bioplastics as a sustainable alternative, emphasizing their biodegradability and renewable origin, but also pointed out challenges, such as production costs and technical limitations. It is concluded that the inclusion of socio-environmental topics in Chemistry education, combined with active methodologies, strengthens students' critical thinking and broadens their awareness of sustainable solutions. The study highlights the importance of innovative pedagogical practices that link science to real-world issues, preparing students for informed and responsible decision-making in the face of contemporary environmental challenges.DOI: https://doi.org/10.56238/sevened2025.026-034